Nanoparticle-based drug delivery systems: a commercial and regulatory outlook as the field matures. (3rd July 2017) - Ragelle, Héloïse; Danhier, Fabienne; Préat, Véronique; Langer, Robert; Anderson, Daniel G.
ABSTRACT: Introduction: Nanomedicine has emerged as a major field of academic research with direct impact on human health. While a first generation of products has been successfully commercialized and has significantly contributed to enhance patient's life, recent advances in material design and the emergence of new therapeutics are contributing to the development of more sophisticated systems. As the field matures, it is important to comprehend the challenges related to nanoparticle commercial development for a more efficient and predictable path to the clinic. Areas covered: The review provides an overview of nanoparticle-based delivery systems currently on the market and in clinical trials, and discuss the principal challenges for their commercial development, both from a manufacturing and regulatory perspective, to help gain understanding of the translational path for these systems. Expert opinion: Clinical translation of nanoparticle-based delivery systems remains challenging on account of their 3D nanostructure and requires robust nano-manufacturing process along with adequate analytical tools and methodologies. By identifying early enough in the development the product critical attributes and understanding their impact on the therapeutic performance, the developers of nanopharmaceuticals will be better equipped to develop efficient product pipelines. Second-generation products are expected to broaden nanopharmaceutical global market in the upcoming years.